Prognostic factors of invasive fungal infections in pediatric intensive care units and changes in treatment outcomes before and after the COVID-19 pandemic: a multicenter retrospective study - Du, Yuhui; Huang, Li; Lu, Xiulan; Su, Jun; Cui, Lidan; Zhang, Qunqun; He, Liming; Li, Tian; Gong, Ling; Lu, Guoping; Cheng, Yibing (Frontiers in Microbiology, 2025)
ObjectiveTo investigate the prognostic factors influencing the outcomes of children with invasive fungal infection in pediatric intensive care unit (PICU) and explore the effects of changes in clinical characteristics before and after the COVID-19 pandemic on treatment outcomes.MethodsIn total, 665 children with invasive fungal infections from the PICUs of four hospitals in China were retrospectively enrolled from January 2017 to December 2021. These children were categorized into an effective treatment group (336 cases) and a failure group (329 cases, including treatment abandonment and death) based on prognosis. Clinical data were compared between the pre-pandemic period (2017–2019, 421 cases) and the post-pandemic period (2020–2021, 244 cases). Univariate and multivariate logistic regression analyses were used to identify the factors related to prognosis.ResultsPrognostic factors: Independent risk factors for treatment failure included agranulocytosis (OR = 3.389, 95% CI 1.518–6.287), hematological malignancies (OR = 3.050, 95% CI 1.544–5.986), blood transfusion (OR = 2.239, 95% CI 1.456–3.442), invasive mechanical ventilation (OR = 1.938, 95% CI 1.158–3.243), and indwelling urinary catheter (OR = 1.750, 95% CI 1.048–2.924). The independent protective factor was identified fungal pathogens (OR = 0.588, 95% CI 0.362–0.956). Pre- and post-pandemic comparisons revealed that the co-infection rate decreased after pandemic (77.9% vs. 70.5%, p < 0.05), the proportion of identified fungal pathogens increased (60.6% vs. 68.0%, p = 0.054), whereas, the treatment failure rate was significantly higher (45.8% vs. 55.7%, p < 0.05). Changes in fungal species after the pandemic: The proportions of Candida and Aspergillus had decreased (89.0% vs. 75.9%, p < 0.05; 8.2% vs. 6.0%, p > 0.05), whereas those of Pneumocystis jirovecii and other fungal species had increased significantly (0.4% vs. 7.8, 2.4% vs. 10.2%, all p < 0.05).ConclusionAgranulocytosis, hematologic malignancies, invasive mechanical ventilation, indwelling urinary catheter and blood transfusion are independent risk factors for adverse outcomes with invasive fungal infections in PICU, and identifying the pathogen can improve outcomes. Post-pandemic changes in fungal species and cumulative risk factors may have offset the potential benefits of reduced co-infection rates, leading to increased treatment failure rates. Therefore, it is necessary to optimize invasive procedure management and provide early coverage for emerging pathogens in high-risk children.